2022
DOI: 10.1002/jmor.21453
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and unbiased stereology of the lateral superior olive in the short‐beaked common dolphin, Delphinus delphis (Cetacea, Delphinidae)

Abstract: In all mammals, the superior olivary complex (SOC) comprises a group of auditory brainstem nuclei that are important for sound localization. Its principal nuclei, the lateral superior olive (LSO) and the medial superior olive (MSO) process interaural time and intensity differences, which are the main cues for sound localization in the horizontal plane. Toothed whales (odontocetes) rely heavily on hearing and echolocation for foraging, orientation, and communication and localize sound with great acuity. The inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 121 publications
0
2
0
Order By: Relevance
“…The superior olivary complex (SOC) is a major computational center in the auditory brainstem that mainly processes inter-aural-difference cues for sound localization. In all mammals, it comprises a group of auditory brainstem nuclei: the lateral superior olive (LSO), the medial superior olive (MSO), the trapezoid body, and peri-olivary nuclei ( 58–60 ).…”
Section: Bidirectional Remodeling Of the Cas Caused By Uadmentioning
confidence: 99%
“…The superior olivary complex (SOC) is a major computational center in the auditory brainstem that mainly processes inter-aural-difference cues for sound localization. In all mammals, it comprises a group of auditory brainstem nuclei: the lateral superior olive (LSO), the medial superior olive (MSO), the trapezoid body, and peri-olivary nuclei ( 58–60 ).…”
Section: Bidirectional Remodeling Of the Cas Caused By Uadmentioning
confidence: 99%
“…For instance, Breathnach (1960) observed that Monakow's striae acousticae, which connect the posterior cochlear nucleus neurons with the lateral lemniscus and the central nucleus of the inferior colliculus, are not apparent, while Held's striae (connecting the VCN and bilateral ventral nuclei of the trapezoid body, superior olivary and perio-livary nuclei) [114] are clearly visible. More recent studies specify morphological cell types (e.g., spherical neurons in the VCN or principal neurons in the lateral superior olive) comparative to terrestrial mammals [115] and provide estimates for the number and density of neurons, and the volume of the VCN and the lateral superior olive [116,117]. See Figure 1 for an overview of the auditory pathways.…”
Section: Central Auditory Pathwaysmentioning
confidence: 99%